ANALISIS TENTANG PEMAHAMAN TRAFFICKING DI KELAS XI SMK AL-MADANI PONTIANAK - Oktavianita, Oktavianita; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstactThis study aims to obtain a description of the analysis of the understanding of class XI trafficking SMK AL- Madani Pontianak. The method used in this study is descriptive method in the form of survey study that is procedur with the problem dselidiki by describing or describing the state of infromasi service about adolescent reproductive health, and explained descriptively. Based on the analysis of the analysis of the understanding of class XI SMI AL-Madani Pontianak 91% trafficking with very good category, it can be concluded that the analysis of understanding of class XI SMI AL-Madani Pontianak trafficking is considered very good. Which means showing that the analysis of understanding the trafficking of class XI SMK AL-Madani Pontianak has been very good.Keywords : Analysis, Traffecking, SMK